NRP1 function and targeting in neurovascular development and eye disease. (May 2016) - Raimondi, Claudio; Brash, James T.; Fantin, Alessandro; Ruhrberg, Christiana
Abstract: Neuropilin 1 (NRP1) is expressed by neurons, blood vessels, immune cells and many other cell types in the mammalian body and binds a range of structurally and functionally diverse extracellular ligands to modulate organ development and function. In recent years, several types of mouse knockout models have been developed that have provided useful tools for experimental investigation of NRP1 function, and a multitude of therapeutics targeting NRP1 have been designed, mostly with the view to explore them for cancer treatment. This review provides a general overview of current knowledge of the signalling pathways that are modulated by NRP1, with particular focus on neuronal and vascular roles in the brain and retina. This review will also discuss the potential of NRP1 inhibitors for the treatment for neovascular eye diseases.